Animal models of nephrotic syndrome - Simić, Ivana; Tabatabaeifar, Mansoureh; Schaefer, Franz (Pediatric nephrology, 2013)
Animal models of proteinuria and nephrotic syndrome are essential tools for studying the mechanisms of action of abnormalities in individual components of the podocyte and glomerular basement membrane. In recent years a variety of in vivo models have been developed to elucidate the function of specific podocyte proteins and their role in the pathogenesis of proteinuria and glomerulosclerosis. In this overview of the animal models currently available we discuss their contribution to our mechanistic understanding and their potential use in screening for novel targeted therapies of steroid-resistant nephrotic syndrome.
Published online: 19 December 2012
Gesehen am 12.10.2018